PERAN KEPEMIMPINAN NASIONAL DALAM MEMBANGUN STABILITAS SOSIAL DAN POLITIK DI INDONESIA - Mushaddaq, Rakha Muna; Nurhuda, Anwar; Rahman, Rusyda Nasyita; Agustinova, Danang Ade (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Adaptive leadership, quality education, and inclusive policies serve as the foundationfor building social and political stability. This study aims to analyze the role of thesethree elements in fostering a harmonious and peaceful society in Indonesia. Aqualitative approach was employed, drawing on relevant literature and secondarydata. The findings indicate that adaptive leadership effectively addresses social andeconomic dynamics, quality education supports character and skill development, whileinclusive policies encourage the participation of various groups in developmentprocesses. The collaboration among these elements creates an environment conduciveto economic growth, security, and social welfare. Therefore, visionary and responsiveleadership strategies are key to Indonesia’s sustainable development in the future.